Foreign capital impact on insurance market development in EU-15 countries - Sławomir Bukowski; Marzanna Lament (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: The objective of the article is to investigate how foreign capital influenced the development of insurance markets in EU-15 countries. Research Design & Methods: A critical review of literature is undertaken, contents of factors which influence development of insurance markets are analysed, and econometric methods are applied. A panel model is constructed and results of its estimation are analysed. Findings: Insurance markets in particular countries develop under the influence of many factors. The share of foreign insurance companies is treated as a structural factor. There is previous research into this subject was conducted, whose results do not confirm a clear impact of foreign capital on the insurance market's development. The study indicates that the development of insurance markets - measured with the penetration rate and with the ratio of insurance density - is affected by shares of foreign capital in life insurance companies. Implications & Recommendations: To verify the hypothesis concerning the impact of foreign capital on the development of insurance markets, scholarship requires further studies of another group of countries (insurance markets). Contribution & Value Added: This study will contribute to the development of theories concerning factors of the development of insurance markets.
Keywords: F3; F4; G2; O04; 330; international finance; insurance market; insurance companies; foreign capital; panel data model; random estimation